LEGAL REGULATION OF THE ACTIVITIES OF SPORTS REPRESENTATIVES - Yo’ldoshev Raxmatjon Ahadjon o’g’li, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article analyzes the processes of legal assessment of the work activities of Representatives (employees) of sports activities in the field of sports and the contractual and legal regulation of these processes. Also, suggestions are made based on the analytical results obtained.